Implementation of Household Waste Management Policy in Cirebon Regency - Jihan Nur Azizah; Afini Afriliza Putri; Moh. Taufik Hidayat; Mahendra Haryo Bharoto (Interdisciplinary Social Studies, 2025)
This research is motivated by the problem of household waste management problems that continue to be a challenge in various regions, especially Cirebon Regency. This study aims to examine the implementation of household waste management policies in Cirebon Regency using Edward III's policy implementation theory with a focus on analyzing policy implementation and identifying indicators that encourage and hinder the process. This research uses a descriptive qualitative approach. Data sources were collected through a series of in-depth interviews, field observations, and documentation. The results showed that the implementation of the household waste management policy in Cirebon Regency had not reached the optimal level. Some of the obstacles found include low public awareness in waste segregation and disposal, limited waste management infrastructure, and lack of government awareness regarding household waste management. This study recommends the need to strengthen waste management infrastructure, improve the household waste management system, improve household waste management education programs to the community, and improve a more effective coordination system between stakeholders to determine the extent of the policy implementation and determine the aspects that contribute to the success of household waste management policies in Kedawung District, Cirebon Regency.